2022
DOI: 10.1155/2022/3167581
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and Physicochemical Characterization of Irrigation Water in Market Gardening in Korhogo

Abstract: Several sources of water are used by farmers without concern for quality, which can have consequences on the health of the consumer of market garden products. The aim of this study is to evaluate the microbiological and physicochemical qualities of irrigation water. Microorganisms were counted using the membrane filtration and incorporation into the agar methods. The physicochemical parameters were measured using multiparameter and spectrophotometric methods. The average values of the physicochemical parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…gambiae ss in almost all sentinel sites in Côte d'Ivoire [22],.Regarding the ace-1 gene, which is responsible for strong resistance to carbamates in populations of the An. gambiae s.l complex, it was found at a low frequency in all sites [23]. The resistance to pyrethroids observed in the sentinel sites located in the north of Côte d'Ivoire corroborates a recent study carried out in Korhogo that showed that An.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…gambiae ss in almost all sentinel sites in Côte d'Ivoire [22],.Regarding the ace-1 gene, which is responsible for strong resistance to carbamates in populations of the An. gambiae s.l complex, it was found at a low frequency in all sites [23]. The resistance to pyrethroids observed in the sentinel sites located in the north of Côte d'Ivoire corroborates a recent study carried out in Korhogo that showed that An.…”
supporting
confidence: 87%
“…Korhogo is the fourth largest city in Côte d'Ivoire in terms of population and economy [11]. It is in the northern part of the country, 635 km from Abidjan, at 9°53'N and 6°49'W.…”
mentioning
confidence: 99%
“…In Ghana, studies on the quality of water used for irrigation for vegetable and crop production in general have indicated different forms of contamination (Abdallah & Mourad, 2021;Amuah et al, 2022;Mayilla et al, 2015). There are the same indications in studies conducted in Cote D'Ivoire (Kambire et al, 2022;Koffi et al, 2012). These findings in Ghana and Cote D'Ivoire, for instance, corroborate assertions made by Amoah et al (2016) that 10% of urban residents in sub-Saharan Africa use wastewater for crop irrigation and that 50%-90% of urban residents in West Africa have eaten vegetables produced with waste or contaminated water.…”
Section: Introductionmentioning
confidence: 79%
“…E. coli is widely used as an indicator of faecal contamination in waterways. Kambire et al [43] stated that water used to irrigate market gardening contained high microorganism loads ranging from 3.64 to 4.35 log cfu/100 mL, 2.44 to 3.31 log cfu/100 mL, 2.44 to 2.9 log cfu/100 mL, and 2.07 to 3.63 log cfu/100 mL for total coliforms, E. coli, faecal enterococci and sulphite-reducing clostridia, respectively while mean loadings of mesophilic aerobic bacteria, moulds and yeasts ranged from 4.95 to 5.98 log cfu/100 mL, 1.8 to 2.08 log cfu/100 mL and 1.5 to 1.98 log cfu/100 mL, respectively. Four different mould strains belonging to the genus Aspergillus were also found in the irrigation water.…”
Section: Microbial Loadmentioning
confidence: 99%